# math

how to you find a composite function form of y in this problem?

y = 1/[(x^2+3x-5)^3]

I don't understand your question. Composite functions require two functions. You listed one. Please amplify.

That's what I thought at first. But I am thinking I might need to substitute y in place of x and x in place of y?

1. 👍 0
2. 👎 0
3. 👁 172

## Similar Questions

1. ### Math22

1. Write the composite function in the form f(g(x)). [Identify the inner function u = g(x) and the outer function y = f(u).] y= (g(x), f(u)) = 2. Write the composite function in the form f(g(x)). [Identify the inner function u =

asked by Anonymous on October 7, 2014
2. ### CAL

Hi, im lost in theses three problems. Please help. Thank you so much!!! 1. Write the composite function in the form f(g(x)). [Identify the inner function u = g(x) and the outer function y = f(u).] y = 3 squareroot all 1 + 5x

asked by Anonymous on October 7, 2014
3. ### Calculus. I need help!

Write the composite function in the form f(g(x)). [Identify the inner function u=g(x) and the outer function y=f(u).] Then find the derivative dy/dx. y=√sinx √ is square root.

asked by danny on February 25, 2012
4. ### functions

For each problem, construct two composite functions, . Evaluate each composite function for x=2 ok i have not dealt with composite functions can I please get some help with this as I have 20 questions to do can someone show me

asked by Johnathan on October 18, 2013
5. ### algebra functions

can someone please check my answer For each problem, construct two composite functions, . Evaluate each composite function for x=2 f(x)=3x g(x)=1/x f(g)*(x)=3x(1)/x x=2 3x(1)/x=6 g(f)*(x)=(3x)=2*3x=6 x=2 3*(2)=6*6=36

asked by tani on October 17, 2013
6. ### algebra functions check my answer

For each problem, construct two composite functions, . Evaluate each composite function for x=2 f(x)=3x g(x)=1/x f(g)*(x)=3x(1)/x x=2 3x(1)/x=6 g(f)*(x)=(3x)=2*3x=6 x=2 3*(2)=6*6=36

asked by tani on October 17, 2013
7. ### math

how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look like so.... x^2(x+3) adam, there's a slight problem with your notation in the expression y = f(x+3). Ordinarily we wouldn't put an expression in place of a

8. ### calculus

Suppose that f(x)= square root of x and g(x)= 3x-4 and you are asked to evaluvate the composite function f(g(0)). What is the complication that occurs in trying to find that composite function value? For waht values of x is it

asked by Pauline on February 3, 2011
9. ### maths

(a)(i)use the composite rule to differentiate the function f(x)=(x^2-6x+23)^(3/2). (ii)use the composite rule and your answer to part (a)(i) to show that the function g(x)=(x-2)/(x^2-6x+23)^(3/2) has derivative

asked by alan on May 20, 2011
10. ### college algebra

Let f(x) = square root (x + 2) and g(x) = x^2 − 2. Determine the domain of the composite function. (Enter your answer using interval notation.) f compose f ______? & Find the composite function. (f compose f)(x) = _____?

asked by Dee on October 21, 2013

More Similar Questions